Tracking the edge of the south seasonal polar cap of Mars - Giuranna, M.; Formisano, V.; Grassi, D.; Maturilli, A. (Planetary and Space Science, 2007)
The advance and retreat of the polar caps were one of the first observations that indicated Mars had seasons. Because a large portion of the atmosphere is cycled in and out of the seasonal caps during the year, the frost deposits play a significant role in regional and global atmospheric circulation. Understanding the nature of the seasonal polar caps is imperative if we are to understand the current Martian climate. In this study, we track the seasonal cap edges as a function of season and longitude for the fall and winter seasons (MY27), using data from the Planetary Fourier Spectrometer (PFS) onboard the Mars Express (MEX) ESA mission. Making use of the rapid rise (decrease) in surface temperature that occurs when CO 2 ice is removed (deposited), in a first approach, we defined the advancing cap edge to be where the surface temperature drops below 150 K, and the retreating cap edge where the surface temperature rises above 160 K. In this case, starting from Lsnot, vert, similar50°, the edge progression speed start to be longitude dependent. In the hemisphere that extends form the eastern limit of the Hellas basin to the western limit of the Argyrae basin (and containing the two) the edges progression speed is about a half than that of the other hemisphere; the cap is thus asymmetric and, unexpectedly, no CO 2 ice seems to be present inside the basins. This is because the above mentioned surface temperatures used in this approach to detect the cap edges are not adequate (too low) for the high-pressure regions inside the basins where, following the Clausius–Clapeyron's law, the CO 2 condensation temperature can be several degrees higher than that of the adjacent lower-pressure regions. In the second, final approach, special attention has been given to this aspect and the advancing and retreating cap edges are defined where, respectively, the surface temperatures drop below and rise above the CO 2 condensation temperature for the actual surface pressure values. Now, the results show an opposite situation than the previous one, with the progression speed being higher and the cap more extended (up to −30° latitude) in the hemisphere containing the two major Martian basins. During the fall season, up to Lsnot, vert, similar50° the South Martian polar cap consists of CO 2 frost deposits that advance towards lower latitudes at a constant speed of 10° of latitude per 15 degrees of Ls. The maximum extension (−40° latitude) of the South polar cap occurs somewhere in the 80°–90° Ls range. At the winter solstice, when the edges of the polar night start moving poleward, the cap recession has already started, in response to seasonal changes in insolation. The CO 2 ice South polar cap will recede with a constant speed of not, vert, similar5° of latitude every 25° degrees of Ls during the whole winter. The longitudinal asymmetries reduce during the cap retreat and completely disappear around Ls=145°.